2013
DOI: 10.1002/ibd.23007
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype–Genotype Profiles in Crohnʼs Disease Predicted by Genetic Markers in Autophagy-Related Genes (GOIA Study II)

Abstract: A multilocus approach using autophagy-related genes provides insight into CD phenotype-genotype associations and genetic markers for predicting therapeutic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The titles and abstracts of the articles were reviewed and 53 articles were subsequently excluded; the full texts and data integrity for the remaining articles were reviewed and a further 47 studies were excluded. Finally, seven case-control studies were included in the present meta-analysis (1720,2527), with publication years that ranged from 2008 to 2013. The selection process of the eligible studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The titles and abstracts of the articles were reviewed and 53 articles were subsequently excluded; the full texts and data integrity for the remaining articles were reviewed and a further 47 studies were excluded. Finally, seven case-control studies were included in the present meta-analysis (1720,2527), with publication years that ranged from 2008 to 2013. The selection process of the eligible studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The titles and abstracts of all articles were reviewed and 53 were excluded; full texts and data integrity were then reviewed and another 51 papers were excluded. A total of 11 case-control studies were included in this meta-analysis (Roberts et al, 2008;Amre et al, 2009;Dema et al, 2009;Latiano et al, 2009;Meggyesi et al, 2010;Wolfkamp et al, 2010;Prager et al, 2012;Wang et al, 2012;Zheng and Pang, 2012;Durães et al, 2013;Moon et al, 2013). Publication years of the eligible studies ranged from 2008-2013.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…Autophagy-related genes (ATG16L1, IRGM) and genes encoding pattern-recognition receptors (e.g. NOD2), were identified as CD susceptibility loci/genes by genomewide association studies [15][16][17], suggesting an important contribution of innate immunity in CD immunopathology. Although it has been known that normal intestinal macrophages show low proinflammatory activity, it has been shown that in intestinal diseases, particularly in CD, their profile differs considerably [13].…”
Section: Introductionmentioning
confidence: 99%